TINJAUAN PENGANGKATAN PEJABAT DI LINGKUP PEMERINTAHAN DKI JAKARTA (PENGANGKATAN SYAMSUDDIN LOLOGAU SEBAGAI WALIKOTA JAKARTA UTARA): Juridical Review of the Appointment of Officials in the Administration of DKI Jakarta (Appointment of Syamsuddin Lologau as Mayor of North Jakarta) - Regita, Angeline; Syam, Radian (Faculty of Law, Universitas Trisakti, 2024)
Regional Autonomy as the implementation of the decentralization system there is delegation of authority given to regional governments to achieve the goals of each region, the regional head is tasked with leading the course of regional autonomy, the appointment of regional heads such as mayors who are not in accordance with statutory regulations can invite various conflicts. The formulation of the problem is what is the mechanism for appointing a mayor based on election regulations and whether this mechanism is in accordance with the mechanism for appointing Syamsuddin Lologau as mayor of North Jakarta. The purpose of this study is to describe the mechanism for appointing Mayors based on election regulations for DKI Jakarta Province and to analyze the appointment of Syamsuddin Lologau as Mayor of North Jakarta. This type of research uses normative legal research, is descriptive and explanatory, uses primary data and secondary data, qualitatively analyzed by drawing conclusions using deductive logic. Based on the appointment of the mayor of North Jakarta, Syamsuddin Lologau, it can be concluded that there was a violation of this appointment and the government should have regulated more clearly regarding the implementation of the mechanism for appointing officials and there is transparency regarding decisions regarding appointments within the scope of the state civil apparatus.